Sevoflurane induces endoplasmic reticulum stress mediated apoptosis in hippocampal neurons of aging rats. - Gang Chen; Ming Gong; Min Yan; Xiaoming Zhang (PLoS ONE, 2013)
Elderly patients are more likely to suffer from postoperative memory impairment for volatile anesthetics could induce aging neurons degeneration and apoptosis while the mechanism was still elusive. Therefore we hypothesized that ER stress mediated hippocampal neurons apoptosis might play an important role in the mechanism of sevoflurane-induced cognitive impairment in aged rats. Thirty 18-month-old male Sprague-Dawley rats were divided into two groups: the sham anesthesia group (exposure to simply humidified 30-50% O2 balanced by N2 in an acrylic anesthetizing chamber for 5 hours) and the sevoflurane anesthesia group (received 2% sevoflurane in the same humidified mixed air in an identical chamber for the same time). Spatial memory of rats was assayed by the Morris water maze test. The ultrastructure of the hippocampus was observed by transmission electron microscopy (TEM). The expressions of C/EBP homologous protein (CHOP) and caspase-12 in the hippocampus were observed by immunohistochemistry and real-time PCR analysis. The apoptosis neurons were also assessed by TUNEL assay. The Morris water maze test showed that sevoflurane anesthesia induced spatial memory impairment in aging rats (P<0.05). The apoptotic neurons were condensed and had clumped chromatin with fragmentation of the nuclear membrane, verifying apoptotic degeneration in the sevoflurane group rats by TEM observation. The expressions of CHOP and caspase-12 increased, and the number of TUNEL positive cells of the hippocampus also increased in the sevoflurane group rats (P<0.05). The present results suggested that the long time exposure of sevoflurane could induce neuronal degeneration and cognitive impairment in aging rats. The ER stress mediated neurons apoptosis may play a role in the sevoflurane-induced memory impairment in aging rats.